Capturing the Price Volatility of Onion and Potato in Selected Markets of Gujarat - Sharma, Hemant; Kalankar, S S; Raykundilya, D P; Makwana, M (Annals of Arid Zone, 2021)
The study investigates four selected markets of onion and potato for capturing the price volatility. The monthly wholesale price data were used for study of price behavior. The results indicated that a negative trend in arrival was observed in Ahmedabad and Vadodara market and price trends was positive in both the commodities. In seasonal indices, fluctuation in the monthly indices of onion and potato arrivals was more than the monthly indices of their prices in selected markets during the study period. Potato crop observed relatively more stability as compared to onion in the selected markets. The results confirmed that there was high volatility in prices of onion in these selected markets as compared to potato. Policies need to be developed to control the volatile nature of onion prices, which is directly affecting people in the low income group.Key words: Onion, potato, wholesale price, Gujarat.